44.6k views
1 vote
Solve for f.
-f + 2 + 4f = 8 - 3
f=​

2 Answers

3 votes

Answer:

f=1

Explanation:

-f+2+4f=8-3

First what you want to do i that you want to simplify as best as you can.

-f+2+4f=8-3 becomes 3f+2=8-3 because you add the 4f to the -1f.

Then, just subtract 2 from both sides to get 3f=8-5

Now, simplify even more

3f=8-5 becomes 3f=3

It should be easy now, but if you still need help, divide

f=1

User Mohammedkhan
by
6.3k points
4 votes

Answer:

1

Explanation:

-f + 2 + 4f = 8 - 3

3f = 6 - 3

3f = 3

f = 1

User Parakmiakos
by
5.3k points